Sosialisasi Rumah Aman dan Sehat Layak Huni Kepada Kelompok Masyarakat Kelurahan Langkai Kecamatan Pahandut Kota Palangka Raya : Penelitian - Ni Putu Diah Agustin Permanasuri; Mega Kurniawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service initiative was implemented to enhance public understanding and awareness of the importance of safe, healthy, and habitable housing. A house is a fundamental human need that functions not only as a place of shelter but also as a space that shapes family character, health, and overall well-being. Observations conducted in Langkai Subdistrict, Pahandut District, Palangka Raya City, revealed that several residential units still do not meet the criteria for healthy housing, including inadequate ventilation, limited natural lighting, substandard sanitation, and the use of building materials that may pose health risks. Through outreach activities grounded in the Transformative Learning Theory, residents were actively engaged in the learning process via educational sessions, group discussions, field simulations, and direct mentoring. The results indicate a 30% increase in community knowledge regarding the concept of safe and healthy housing. Additionally, positive behavioural changes were observed, such as improved environmental cleanliness, enhanced ventilation, and better household waste management. The community also established a self-help group focused on sustainably maintaining environmental hygiene and safety. Overall, this initiative proved effective in raising public awareness and fostering community self-reliance in creating healthier and safer residential environments.